Assessment of Long‐Term Soil Erosion in a Mountain Vineyard, Aosta Valley (NW Italy). (25th January 2017) - Biddoccu, Marcella; Zecca, Odoardo; Audisio, Chiara; Godone, Franco; Barmaz, Andrea; Cavallo, Eugenio
Abstract: In the mountain region of Aosta Valley, NW Italy, grapevine were, in the past, traditionally grown on terraces supported by dry stone walls. Since the 1960s, terrace systems were gradually abandoned in favour of an up and down slope row orientation. Tillage and chemical weeding are common soil management techniques adopted in vineyards with high slope gradient, to maintain bare soil. Both techniques expose, to varying degrees, the soil to degradation, favouring runoff and soil losses. Although many studies have focused on the effects of soil water erosion in vineyards, there is still a gap in the evaluation of long‐term soil erosion rates in vineyards located on very steep slopes (higher than 35%). In order to evaluate long‐term soil erosion on a very steep vineyard, a study was carried out on a 44‐year‐old vineyard located at about 900 m asl. The vine rows were oriented up and down the slope, which is about 50% (29°). The inter‐row soil management of the vineyard included chemical weeding and, in the first year after plantation, the adoption of irrigation and hilling‐up / taking‐out the soil around the vines. The soil loss was determined adopting the technique of botanical benchmark. According to this methodology, the estimated total soil lost over 44 years was about 692 Mg ha −1, with average annual soil loss of 15·7 Mg ha −1  year −1, confirming that the water and management practices adopted in the vineyard, besides the high slope gradient, have played a relevant role in determining the high erosion rate. Copyright © 2016 John Wiley & Sons, Ltd.